(untitled) (Al-Qamar, 2020)
Islamic law has number of sources. Basic sources are Qur’ān and Ḥadīth, while Ijmā‘(scholarly consensus), Qiyās (analogical reasoning), Istiḥsān (juristic preference), Ijtihād (independent reasoning), Istiṣlāḥ (public interest) Istiṣḥāb (presumption of continuity), and ‘Urf (common sense) are secondary sources. This paper studies the use of the principle of Istiḥsān in the Sharīʻah legitimacy of Contemporary Issues. Istiḥsān is used to resolve the issues based on human needs and expedients in cases when apparent analogy or common rules do not correspond with the universally accepted purposes of Sharī‘ah. In such cases, the apparent analogy is left to adopt a way that corresponds to the objectives of Sharī‘ah. This process is known as Istiḥsān (juristic preference). The new order is declared Ḥasan or Mustaḥsan which may increase the public welfare and remove the harm and which may become harmonious to the divine wisdom. The Paper finds that Islamic jurisprudence is not a collection of strict rules which cannot present solution of new queries in the changing circumstances. It is fully capable of fulfilling religious and social needs of the people in all situations. Principle of Istiḥsān has the capacity to present solution of different human questions that appear due to change of time and place.